2017
DOI: 10.1542/peds.2016-3353
|View full text |Cite
|
Sign up to set email alerts
|

Receptivity to Tobacco Advertising and Susceptibility to Tobacco Products

Abstract: BACKGROUND AND OBJECTIVES: Non-cigarette tobacco marketing is less regulated and may promote cigarette smoking among adolescents. We quantified receptivity to advertising for multiple tobacco products and hypothesized associations with susceptibility to cigarette smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
102
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(113 citation statements)
references
References 30 publications
4
102
4
Order By: Relevance
“…This high level of awareness by adolescents may translate into increased susceptibility to use e-cigarettes and potentially cigarettes or other tobacco products, a topic that has been investigated in a separate paper. 34 Future waves of the PATH Study will provide the longitudinal data necessary to solidify our understanding of adolescent susceptibility, receptivity to marketing, and uptake of tobacco products.…”
Section: Discussionmentioning
confidence: 99%
“…This high level of awareness by adolescents may translate into increased susceptibility to use e-cigarettes and potentially cigarettes or other tobacco products, a topic that has been investigated in a separate paper. 34 Future waves of the PATH Study will provide the longitudinal data necessary to solidify our understanding of adolescent susceptibility, receptivity to marketing, and uptake of tobacco products.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings have important implications for interpretation of results from cross-sectional studies of older adolescents that use the susceptibility to cigarette index as a surrogate for future cigarette initiation (e.g., (Pierce et al, 2017; Trinidad et al, 2017)). Because the susceptibility to smoking index is unable to distinguish future smokers from non-smokers among youth who have used e-cigarettes, studies attempting to use the susceptibility index as a marker of future smoking should interpret results with caution.…”
Section: Discussionmentioning
confidence: 88%
“…It is worldwide recognized that pro-tobacco messages, including tobacco advertising and promotions in movies, magazines and other media [26]has an impact on promoting youth smoking. Tobacco industries take advantage of advertisements to arouse adolescents' interest in tobacco use [27], through shaping their perceptions of smoking norm, and perceived benefits and smoking risks [7]. Previous studies [28]showed that exposure to Point-of-sale (POS)promotion was associated with 1.6 and 1.3 times higher odds of experimental smoking and smoking susceptibility respectively among adolescents [10].…”
Section: Discussionmentioning
confidence: 99%